Modeling the Dynamics of Dengue Transmission with Awareness and Optimal Control Analysis. - Faishal F Herdicho; F Fatmawati; Cicik Alfiniyah; Farah P Fajrin; Ebenezer Bonyah; Muhammad A Rois; Olumuyiwa J Peter (PLoS ONE)
Dengue fever is a vector-borne disease which is transmitted by the bites of mosquitoes infected with dengue viruses. This disease is spread around the world and still as a global health problem. In this work, we formulate the dengue model by considering the population of aware humans. The real data of dengue infection in East Java, Indonesia is employed to estimate the parameters of the dengue model. The estimation of parameters is done by using monthly cumulative data on humans infected dengue that recorded at East Java Health Office on 2018-2020. We then analyze the stability of the equilibria of the model. The analysis exhibits that the disease-free equilibrium is locally and globally asymptotically stable when the basic reproduction number is less than one. We utilize the Lyapunov function approach to guarantee that the endemic equilibrium is globally asymptotically stable whenever the reproduction number is greater than one. Furthermore, this work examines the effectiveness of various dengue control strategies, including vector control, awareness program, and prevention. Cost-effectiveness evaluation has shown that the combination of vector control, awareness programs, and awareness prevention is the most effective intervention to reduce the dengue fever in the community.